Proceedings IEEE INFOCOM 2006. 25TH IEEE International Conference on Computer Communications 2006
DOI: 10.1109/infocom.2006.253
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Contention Based Medium Access Control Protocols

Abstract: We study the performance of contention based medium access control (MAC) protocols. In particular, we provide a simple and accurate method for estimating the throughput of IEEE 802.11 DCF and IEEE 802.11e EDCA. Our method is based on a rigorous analysis of the Markov chain associated with the back-off process at the contending nodes. Our results provide new insights into the operation of IEEE 802.11 DCF and IEEE 802.11e EDCA. Although we focus on IEEE 802.11 MAC protocol in this paper, the techniques developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…We also stress that the stability condition established in this work for the first time has been tantalizing other researchers as well, e.g., [17,Appendix B].…”
Section: Q:"under Which Conditions Is the Fpe Valid?"supporting
confidence: 60%
See 1 more Smart Citation
“…We also stress that the stability condition established in this work for the first time has been tantalizing other researchers as well, e.g., [17,Appendix B].…”
Section: Q:"under Which Conditions Is the Fpe Valid?"supporting
confidence: 60%
“…The need of a proof for finite K is stressed in [1, pp.833] due to its practical implication. In line with this, by appealing to a Lyapunov function, Sharma et al proved this for the case K = 1 where there are only two backoff stages [17,Lemma 3].…”
Section: Validation Of Decoupling Assumption: Ode Modelmentioning
confidence: 89%
“…Our cross-layer WLAN models may be viewed as advancing the station-centric Markov chain analysis approach followed by Bianchi [5] whose surprisingly accurate performance predictions are only now being better understood [24]. Our results show that modular station-centric Markov modeling-even when the underlying Markov chains for ARF, DCF, and TCP are very different-can accurately capture WLAN performance in the presence of cross-layer interactions.…”
Section: B New Contributionmentioning
confidence: 77%
“…A multi-rate generalization of Bianchi's model has been considered in [32], albeit with the severe restriction that stations are assigned fixed data rates. An interesting technical advance is a Markov chain model over the state-space counting the number of stations in a backoff stage [24] that trades Bianchi's independence assumption with stochastic approximation using average (i.e., deterministic) dynamics. The results are relevant because they help explain why the independence assumption leads to accurate quantitative predictions, a hallmark of Bianchi's Markov chain model.…”
Section: Related Workmentioning
confidence: 99%
“…A wealth of applications to specific case studies can be found in the literature; for instance to MAC protocols [8,38], TCP protocols [1,2], peer-to-peer networks [36], caching algorithms [27] and load balancing strategies [21,22].…”
Section: Related Workmentioning
confidence: 99%